The process of flushing the gravitational cleaner from pollution cleansers - Пузік, С.О.; Манзій, В.С.; Закревський, В.О.; Шевчук, В.С. (Proceedings of National Aviation University (archive), 2010)
During the dirt accumulation the operating efficiency of the cleaners is decreasing and can be restored by cleaning the surface of sedimental plates cleaner. The condition of washing cleaner from pollution is excess of stokes forces on sliding friction force and size that characterizes the roll friction. Inequalities for all computed values of stoke strength were arranged and solved relative to waste of certain cleaning fluids. Thus: the flushing gravity cleaner with considered detergents is possible, more efficient process is to wash with detergent that has higher kinematic viscosity coefficient.